2021
DOI: 10.17532/jhsci.2020.1156
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine for COVID-19: A Potential Adjuvant Therapy

Abstract: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV2) infection or known as coronavirus disease 2019 (COVID-19) is a highly infectious disease that has been declared as a world pandemic by WHO. Although the majority of patients only experience mild symptoms, older patients and those with comorbidities are in the risk of falling into critically ill and even death. This is thought to correlate with systemic inflammatory response and oxidative stress imbalance. N-acetylcysteine (NAC) is recognized as a pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…If there is a higher demand for GSH because of oxidative stress, such as during viral infection [ 102 ], extreme or endurance exercise [ 103 ], and hypoxic conditions [ 22 , 94 ], it will have an inhibitory effect on inorganic sulfate synthesis. Lowered redox potential, common in high-risk COVID-19 patients, including older adults and those with uncontrolled DM, causes alterations in the TNF α receptor activity towards a proinflammatory state [ 22 , 31 , 95 ]. It is known that infection by RNA-viruses induces oxidative stress in host cells, and growing evidence indicates that viral replication is regulated by the redox state of the host cell [ 30 , 94 , 104 , 105 ].…”
Section: Nac As a Physiological Precursormentioning
confidence: 99%
See 3 more Smart Citations
“…If there is a higher demand for GSH because of oxidative stress, such as during viral infection [ 102 ], extreme or endurance exercise [ 103 ], and hypoxic conditions [ 22 , 94 ], it will have an inhibitory effect on inorganic sulfate synthesis. Lowered redox potential, common in high-risk COVID-19 patients, including older adults and those with uncontrolled DM, causes alterations in the TNF α receptor activity towards a proinflammatory state [ 22 , 31 , 95 ]. It is known that infection by RNA-viruses induces oxidative stress in host cells, and growing evidence indicates that viral replication is regulated by the redox state of the host cell [ 30 , 94 , 104 , 105 ].…”
Section: Nac As a Physiological Precursormentioning
confidence: 99%
“…Oxidative processes enhance viral infection by promoting replication in infected cells, inhibition of cell proliferation, and cell apoptosis induction [ 35 , 95 ]. Studies found that NAC treatment significantly reduced the frequency of influenza in the elderly and the severity and duration of most symptoms [ 31 , 95 , 160 , 162 ]. To replicate, RNA-viruses need active NF- κ B pathway support within host cells [ 158 ].…”
Section: Nac As a Therapeutic Agentmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanisms of NAC therapy for COVID-19 include: 1. inhibiting the envelope (E) protein and thorn (s) protein of the virus and reducing its binding to angiotensin II receptors (AT2R); 2. inhibiting angiotensin-converting enzyme (ACE); 3. inducing the synthesis of endogenous GSH so as to enhance antioxidation and reduce intracellular protein glycosylation; and 4. inhibiting the production of proinflammatory mediators and cytokines (12). In addition, high-dose intravenous NAC is reported to play a key role in the treatment of severe cases of COVID-19 (3,13,14).…”
mentioning
confidence: 99%